Fibrotic Response as a Distinguishing Feature of Resistance and Susceptibility to Pulmonary Infection with Mycobacterium tuberculosis in Mice - Marquis, Jean-François (American Society for Microbiology (ASM), 2008)
The differential susceptibility of inbred mouse strains DBA/2J (susceptible) and C57BL/6J (resistant) to pulmonary tuberculosis following aerosol infection is under complex genetic control. In this report, transcriptional profiling with RNAs from Mycobacterium tuberculosis-infected lungs was used to investigate the physiological response, cell type, and biochemical pathways underlying differential susceptibility to infection. Statistical analysis of cDNA-based microarrays revealed that 1,097 transcripts showed statistically significant changes in abundance (changes of ≥1.5-fold) in at least one of four experimental group comparisons (C57BL/6J [day 0] versus DBA/2J [day 0] mice, C57BL/6J [day 90] versus DBA/2J [day 90] mice, C57BL/6J [day 90] versus C57BL/6J [day 0] mice, or DBA/2J [day 90] versus DBA/2J [day 0] mice). A group of genes showing very high degrees of significance (changes of ≥2.0-fold) displayed enrichment for transcripts associated with tissue remodeling and the fibrotic response. The differential expression of fibrotic response genes (Sparc, Col1a1, Col1a2, Col4a1, and Col4a2) in the infected lungs of the two mouse strains was validated by another microarray platform (Affymetrix oligonucleotide chips) and by reverse transcription-PCR. Furthermore, the differential expression of additional genes known to be associated with fibrosis (Mmp2, Timp1, and Arg1) was also validated by these approaches. Overall, these results identify the differential fibrotic response as a pathological basis for the high susceptibility of DBA/2J mice to pulmonary tuberculosis.